Stability enhancement of large scale power systems with nonlinear decentralized controllers - Guo, Guoxiao. (2009)
Improving the stability of synchronous generators under small and large disturbances is one of the most important problems in power system control. The objective of this research project is seeking new control schemes for transient stability enhancement of nonlinear multimachine power systems, including systems with flexible AC transmission system (FACTS) device phase shifters, using direct feedback linearization (DFL) technique, decentralized control methods and robust control theory.